Pengaruh Manajemen Perencanaan Pembelajaran Terhadap Kinerja Guru SMA Negeri di Kota Mataram - Yuniati, Safrida; Prayoga, Sugeng (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2019)
The aim of this study was to know the effect of Learning Planning Management on the performance of high school teachers in the city of Mataram. This study used a quantitative research approach with ex-post facto methods. The population of this study was all of the 137 SMA teachers and SMA 5 Mataram teachers. The research sample consisted of 58 teachers taken using probability sampling techniques. The research instrument used a questionnaire. Data analysis techniques used were statistical analysis, namely simple regression and multiple regression tests. The result of the study showed that Learning Planning Management had a positive effect on the performance of high school teachers in Mataram City by 19.2%. Thus, it can be concluded that the better the planning of learning management, the better performance of high school teachers in the city of Mataram would increase.